2020
DOI: 10.1111/jpi.12698
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates diabetic cardiomyopathy and reduces myocardial vulnerability to ischemia‐reperfusion injury by improving mitochondrial quality control: Role of SIRT6

Abstract: Targeting mitochondrial quality control with melatonin has been found promising for attenuating diabetic cardiomyopathy (DCM), although the underlying mechanisms remain largely undefined. Activation of SIRT6 and melatonin membrane receptors exerts cardioprotective effects while little is known about their roles during DCM. Using high‐fat diet‐streptozotocin‐induced diabetic rat model, we found that prolonged diabetes significantly decreased nocturnal circulatory melatonin and heart melatonin levels, reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 72 publications
2
80
0
Order By: Relevance
“…Previous findings have indicated that hsp22 directly binds to AMPK and promotes its nuclear translocation and phosphorylation at Thr172, which results in a stimulation of survival mechanisms [ 27 ]. Additionally, activators and suppressants of AMPK have been employed to verify that AMPK exerts a protective role in mitochondrial dynamics imbalance and oxidative stress-mediated myocardium [ [50] , [51] , [52] ], brain [ 28 , 53 , 54 ] and liver injury [ 25 ]. But, it is still little known whether hsp22-induced upregulation of p-AMPK is answerable for its protective properties on mitochondrial dysfunction in SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings have indicated that hsp22 directly binds to AMPK and promotes its nuclear translocation and phosphorylation at Thr172, which results in a stimulation of survival mechanisms [ 27 ]. Additionally, activators and suppressants of AMPK have been employed to verify that AMPK exerts a protective role in mitochondrial dynamics imbalance and oxidative stress-mediated myocardium [ [50] , [51] , [52] ], brain [ 28 , 53 , 54 ] and liver injury [ 25 ]. But, it is still little known whether hsp22-induced upregulation of p-AMPK is answerable for its protective properties on mitochondrial dysfunction in SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies have indicated that uncontrolled inflammation and oxidative stress may contribute to cardiac dysfunction in diabetic cardiac tissues (10,11). Extensive research has also revealed that mitochondrial injury may serve as a central mediator in the pathology of DCM (12,13). Therefore, identifying potential therapeutic strategies that target chronic inflammation and oxidative stress may aid in the management of DCM.…”
Section: Introductionmentioning
confidence: 99%
“…The FOXO3a/Bim signaling pathway plays a crucial role in the modulation of I/R-induced cell apoptosis [21,28,29]. Previous studies demonstrated that melatonin inhibits I/R-induced cell apoptosis in many types of cells, including cardiomyocyte [5,6,9]. Importantly, FOXO3a has been shown to serve as an important downstream target of melatonin and mediate melatonin-induced transcriptional regulation of proapoptotic Bim [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-reperfusion (I/R) injury is still one of the primary causes of death in ischemic heart disease [1,2]. Cardiomyocyte apoptosis plays an essential role in acute myocardial I/R injury [3][4][5]. It is well known that cardiomyocytes are vulnerable to energy and nutrition depletion, and they will experience cell death immediately after I/R injury [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation